أثر الرفع التشغيلي على المخاطر المنتظمة (دراسة تطبيقية على الشركات المساهمة المدرجة في السوق المصرية للأوراق المالية) - علي غذوان; ابراهيم سماح (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The aim of this study is to identify the impact of operating leverage on the systemic risks that companies listed in Egyptian Stock Exchange may face and the extent and direction of this impact, As well as the extent of the potential change in the impact of operating leverage on systemic risks, depending on the operating leverage, on the one hand, and on the other, of the systemic risks measures. To achieve this goal, the researcher relied on the positivist philosophy and the deductive approach in the test of the hypothesis of the study. The financial data for the study variables were collected by means of the financial statements of a sample of Egyptian companies containing 22 companies listed on the Egyptian Stock Exchange, from the first quarter of 2010 to the end of the second quarter of 2015. The study reached a number of results, the most important of which are: v There was a significant impact of operating leverage on the systemic risks facing companies listed in Egyptian Stock Exchange. v The effect of the operating leverage on the systemic risks facing Egyptian companies differed according to the operating leverage measures. v The impact of the operating leverage on the systemic risks did not differ according to the systemic risks measures. يهدف هذا البحث إلى التعرّف على أثر الرفع التشغيلي على المخاطر المنتظمة التي يمكن أن تتعرض لها الشركات المدرجة في السوق المصرية للأوراق المالية، ومدى واتجاه هذا التأثير، وكذلك مدى التغير المحتمل لأثر الرفع التشغيلي على المخاطر المنتظمة باختلاف مقاييس الرفع التشغيلي من جهة، وباختلاف مقاييس المخاطر المنتظمة من جهةٍ أخرى. لتحقيق هذا الهدف اعتمدت الباحثة على الفلسفة الوضعية والمنهج الاستنتاجي في اختبار فرضيات الدراسة، وتم جمع البيانات المالية الخاصة بمتغيرات الدراسة عن طريق القوائم المالية لعينة من الشركات المصرية تحوي 19 شركة مدرجة في سوق مصر للأوراق المالية خلال الفترة الممتدة من الربع الأول لعام 2010 وحتى نهاية الربع الثاني لعام 2015. وقد توصلت الدراسة إلى مجموعة من النتائج أهمها: 1) ظهور أثر للرفع التشغيلي على المخاطر المنتظمة التي تواجه الشركات المدرجة في سوق مصر للأوراق المالية. 2) اختلف أثر الرفع التشغيلي على المخاطر المنتظمة التي تواجه الشركات المصرية باختلاف مقاييس الرفع التشغيلي. 3) لم يختلف أثر الرفع التشغيلي على المخاطر المنتظمة باختلاف مقاييس المخاطر المنتظمة.